MASJID KA’BAH SEBAGAI PUSAT DAKWAH (STUDI MASJID KA’BAH PUNCAK SYAFA’AT DUSUN SUMBERURIP DESA BARUREJO KECAMATAN SILIRAGUNG BANYUWANGI) - Abdul Azis; Khotibul Umam; Moch. Nur Afandi (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
The mosque is a building erected for worship to Allah SWT, especially for performing the five daily prayers, Friday prayers, and other worship, also used for Islamic syiar activities, religious education, training and social activities. The purpose of the study was to be able to describe da'wah activities at the Mosque Ka'bah Puncak Syafa'at.To find out the activities of da’wah at the kaaba mosque,the peak of intercession. This research use desciptive qualitative approach. This type of research is used by researchers in order to be able to know and clearly describe what is happening in the field. Based on the results of the research, it can be answered that the formulation of the problem in this research is as follows: Da'wah activities at the Masjid Ka'bah Puncak Syafa'at are divided into several da'wah activities, namely da'wah activities in the form of worship, study groups, social religion and education. Activities in the form of worship include the five daily fardu prayers in congregation, the implementation of Eid al-Fitr and Eid al-Adha prayers, the sunnah prayers of Dhuha Tarawih and Witir. Da'wah activities in the form of study groups, namely recitation of each such as recitation of the book of Ihya ulumidin every after Fajr prayer, religious lectures. Da'wah activities in the form of socio-religious activities such as distributing sacrificial animal meat after Eid al-Adha prayers and distributing Zakat Fitrah to those who are entitled to receive it.